2013
DOI: 10.1007/s10006-013-0412-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intra-space injection of Twin mix versus intraoral-submucosal, intramuscular, intravenous and per-oral administration of dexamethasone on post-operative sequelae after mandibular impacted third molar surgery: a preliminary clinical comparative study

Abstract: Steroid groups had a better clinical outcome with improved quality of life post-operatively when compared to the nonsteroid study group. Intra-space injection of dexamethasone in pterigomandibular space as Twin mix was found to have similar clinical effects as conventional methods of administering steroids via intraoral-submucosal, intramuscular, intravenous and per-oral routes. This, however, is a small study which would now benefit from larger numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 8 publications
3
40
0
Order By: Relevance
“…However, it is a convenient, safe and lowcost route. Our study data showed that oral dexamethasone was effective to control pain and edema during the studied period, which is in line with other similar studies 6,7,11,12 . Submucosal dexamethasone injection had significant effect on edema in two previous studies and both have reported significant decrease of edema in the immediate postoperative period as compared to controls 1,13 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, it is a convenient, safe and lowcost route. Our study data showed that oral dexamethasone was effective to control pain and edema during the studied period, which is in line with other similar studies 6,7,11,12 . Submucosal dexamethasone injection had significant effect on edema in two previous studies and both have reported significant decrease of edema in the immediate postoperative period as compared to controls 1,13 .…”
Section: Discussionsupporting
confidence: 93%
“…An interesting observation in this group was the significant trismus decrease in the first postoperative day, which is similar to group B (oral route), fact which might be result of the higher concentration of dexamethasone obtained immediately at injury site. These results add more power to the concept that dexamethasone administered close to the surgical site is a valuable way to decrease edema and trismus 5,6,12,32 . Our results, regarding Levene and Shapiro-Wilks tests, have not shown statistically significant differences between groups with regard to postoperative pain, edema and trismus decrease after third molar extraction.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations